Genetic Privacy: The Potential for Genetic Discrimination in Insurance - Jensen, Pamela (Victoria University of Wellington Law Review, 1999)
The threat of modern genetics has been perceived as coming, rather dramatically, from genetic engineering, but the less flashy field of medical genetic testing poses significant and immediate issues. This article discusses the potential for breach of confidentiality or invasion of privacy through the acquisition of information, the disclosure of information, and the potential for prejudicial use of that information by third parties. The author concludes that New Zealand's ethical and legal aspects of human genetics needed a review at the time of writing, recommending an advisory group to be set up to monitor developments in human genetics, facilitate discussion with all relevant persons, groups and bodies, and report on issues arising from new developments in human genetics that can be expected to have wider ethical, social, economic, and legal consequences. However, the author does not find it necessary to enact genetic-specific legislation.